2009
DOI: 10.2478/s11536-009-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of antibiotic therapy on pouchitis after ileal pouch anal anastomosis: A systematic review and meta-analysis of clinical trials

Abstract: AbstractThe aim of the study was to evaluate and collect current evidence on the effect of antibiotics in pretreatment of pouchitis after restorative ileal pouch anal anastomosis (IPAA). Pubmed, Embase, Web of Science, Scopus, and Cochrane Library databases were searched between 1966 and July 2008; and relevant clinical trials extracted, reviewed, and validated according to the study protocol. The outcome of interest was clinical improvement after treatment. Nine randomized, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These disparate results highlight the need for additional strategies to identify and characterize disease-inducing bacteria. The non-germ-free approach we used here generates healthy, IBD-susceptible mice by pre-treating conventionally raised animals with antibiotics that have been widely studied in human IBD (Elahi et al, 2009; Ohkusa et al, 2010; Rahimi et al, 2006). We showed that antibiotic treatment eradicates certain bacterial subsets from the microbiota, enabling us to experimentally colonize antibiotic-pretreated animals with primary isolates of commensal bacteria indigenous to our mouse colony and specifically quantify colonization using culture- and molecular-based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These disparate results highlight the need for additional strategies to identify and characterize disease-inducing bacteria. The non-germ-free approach we used here generates healthy, IBD-susceptible mice by pre-treating conventionally raised animals with antibiotics that have been widely studied in human IBD (Elahi et al, 2009; Ohkusa et al, 2010; Rahimi et al, 2006). We showed that antibiotic treatment eradicates certain bacterial subsets from the microbiota, enabling us to experimentally colonize antibiotic-pretreated animals with primary isolates of commensal bacteria indigenous to our mouse colony and specifically quantify colonization using culture- and molecular-based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences of SRUS is infection; that should be taken under consideration. Recently, the role of microbes in inflammatory lesions have raised much interest; the effectiveness of antibiotics and the benefit of probiotics in amelioration of inflammatory conditions in the colon have been confirmed by meta-analyses [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%